The Importance of Measuring Ultrafine Particles in Urban Air Quality Monitoring in Small Cities - Notardonato, Ivan; Manigrasso, Maurizio; Pierno, Luigi; Settimo, Gaetano; Protano, Carmela; Vitali, Matteo; Mattei, Vincenzo; Martellucci, Stefano Martellucci; Di Fiore, Cristina; Boccia, Paolo; Avino, Pasquale (Geographica Pannonica, 2019)
The air quality monitoring is based on the determination of some gaseous pollutants and PM10 and PM2.5. Recent studies have reported the importance of the determination aerosol fraction below 1 µm both for the dynamic of the airborne and for the public health issue. This paper would like to investigate the importance of this fraction in the air quality monitoring. Further, a particular focus will be devoted the role of the Ultrafine Particles, i.e. particles below 100 nm, in the aerosol formation and in the human exposure. Two case studies will be presented and discussed on how the submicron particles can be determined and interpreted their role. In the first case, the measurements will be performed in downtown Rieti, city located in central Italy, 100 km North from Rome, with the scope to draw the behavior in relationship to the emission flexes. In the second scenario, the personal exposure of pedestrians will be investigated in Venafro, a small city located 150 km South-East Rome, by means of measuring PMx, total submicron fraction, different aerosol dimensional sizes in the range 5-360 nm along with the total Volatile Compounds. The different sources and contributions affecting the aerosol levels in the two areas will be investigated and extensively discussed as well as the role of the such particles in the aerosols science.
Keywords: Measuring Ultrafine; Ultrafine; Importance of Measuring; Air; air quality monitoring; Ultrafine Particles; submicron; Particles; air quality; aerosol